Molecular Mechanisms of Bartonella and Mammalian Erythrocyte Interactions: A Review - Deng, Hongkuan; Pang, Qiuxiang; Zhao, Bosheng; Vayssier-Taussat, Muriel (Frontiers in Cellular and Infection Microbiology, 2018)
Bartonellosis is an infectious disease caused by Bartonella species that are distributed worldwide with animal and public health impact varying according to Bartonella species, infection phase, immunological characteristics, and geographical region. Bartonella is widely present in various mammals including cats, rodents, ruminants, and humans. At least 13 Bartonella species or subspecies are zoonotic. Each species has few reservoir animals in which it is often asymptomatic. Bartonella infection may lead to various clinical symptoms in humans. As described in the B.tribocorum-rat model, when Bartonella was seeded into the blood stream, they could escape immunity, adhered to and invaded host erythrocytes. They then replicated and persisted in the infected erythrocytes for several weeks. This review summarizes the current knowledge of how Bartonella prevent phagocytosis and complement activation, what pathogenesis factors are involved in erythrocyte adhesion and invasion, and how Bartonella could replicate and persist in mammalian erythrocytes. Current advances in research will help us to decipher molecular mechanisms of interactions between Bartonella and mammalian erythrocytes and may help in the development of biological strategies for the prevention and control of bartonellosis.